Fostering excellent learning: exploring madrasa teachers’ learning methods into improve students’ Islamic behaviors - Tambak, Syahraini; Abdullah, Mohammad Roshimi; Nurhayati, Nurhayati; Chapakiya, Abdurrohman; Filya, Mardhotillah Putri (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
Research on pesantren has been carried out by many researchers, but the use of the Islamic behavior development method in learning processes is still very much neglected. This study, over a three-year period, explored Islamic behavior learning methods in Islamic boarding schools in Indonesia. Using a phenomenological study approach, this research interviewed teachers from five Islamic boarding schools. Data cleaning, transcripts, coding and categorization, and interpretation were chosen for data analysis. This study showed the Islamic behavior learning method of repressing students’ syahwiya (worldly lust) spirit with habituation in sunnah prayers, qawlan sadidan (firm words) method, and qawlan balighan (right words) method fostering ‘iffah (modest), jud (generous), and syaka’ (philanthropic), amanah (trustworthy), ‘afwu (forgiving), zuhud (care about the afterlife), rahmah (restore the rights of others), and hilm (polite) traits. The learning method in managing hammiya (temper tantrum) spirit uses shiyam (fast) and dzikrullah (meditative prayer to Allah) methods that foster syaja’ah (courageous), jud (generous), hilm (polite), mujahadah (persistence), and sabr (forbearing) behaviors. Nurturing mufakkara (soul thinking) spirit with al-qisah wa al-tarikh (method of learning storytelling and history) and dialog methods that bring forth loving-knowledge and fathanah (clever)-thinking behaviors. This research presents an implication for the theory of “Islamic behavior learning methods” that must be used by madrasah teachers, in addition to strong discussions in improving the morale of the nation's generation